Analysis of Carbon Dioxide Absorption in Solutions of Potassium Salts of Glycine and Sarcosine. - Gu, Yi. (2017)
Abstract: Carbon dioxide absorption in aqueous solutions of amino acid salts (AAS) involves simultaneous mass transfer with multiple reversible chemical reactions. The process is mathematically modeled by a set of nonlinear ordinary differential equations (ODEs) which cannot be solved analytically. However, near-exact solutions may be derived using the "Thick Film" linearization technique developed by K. A. Smith for application to the analysis of carrier-facilitated membrane transport. This technique is a variant of singular perturbation methods and is computationally efficient. In this thesis, the Thick Film analysis is applied, in the context of the Film Model of mass transfer, to calculate rates of absorption of carbon dioxide in solutions of potassium glycinate (PG) and potassium sarcosinate (PS). Calculated enhancement factors, E, by which reaction multiplies absorption rates are in excellent agreement with values obtained via more computation-intensive numerical methods.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Jerry Meldon.; Committee: Nakho Sung, and Christoph Borgers.; Keyword: Chemical engineering.